The effects of forest industry impacts upon tourist perceptions and overall satisfaction. Issue 2 (3rd April 2017) - Hilsendager, Kyle; Harshaw, Howard; Kozak, Robert
ABSTRACT: Due to the growth of nature-based tourism during in recent decades, the value of forested areas for the tourism industry has been increasing. This is largely due to the aesthetic values that are often associated with forests. However, forests are also highly valued for timber production, an activity that can seriously compromise the visual quality of forested landscapes. Therefore, this article examines the effect that forest industry impacts have upon tourist perceptions and overall satisfaction in destinations that promote natural landscapes to attract visitors. To help understand this issue, tourists were surveyed at natural attractions in Vancouver Island, Canada and Tasmania, Australia. Results suggest that certain forest industry impacts do have the potential to negatively impact upon tourist perceptions in the two destinations included for this analysis. However, there appear to be a number of additional elements that are also important for shaping the perceptions of tourists, as overall satisfaction ratings were shown to be quite high for both Vancouver Island and Tasmania.